Seismic behavior of exposed concrete filled steel tube column bases with embedded reinforcing bars: Experimental investigation. (March 2019) - Qiao, Qi-yun; Zhang, Wen-wen; Mou, Ben; Cao, Wan-lin
Abstract: In this study, an innovative exposed concrete filled steel tube (CFST) column base with embedded reinforcing bars is proposed. Based on the conventional exposed CFST column base comprised of a base plate and anchor rods, additional reinforcing bars are embedded in the proposed column base. Eight column bases are fabricated and tested under constant axial loading and horizontal cyclic loading. The test parameters include the width-to-thickness ( B / t ) ratio of the steel tube, axial force ratio, with or without embedded reinforcing bars, and two different types of the base plates. Failure modes, hysteretic curves, strength and stiffness, cyclic behavior and strain characteristics are discussed and analyzed. The results show that the strength, stiffness and energy dissipation of the new column bases with embedded reinforcing bars are considerably greater than those of the conventional exposed CFST column bases. The difference in base plate types leads to a slight difference in seismic behavior of the column bases; however, both types of specimens have stable and sufficient seismic behavior, and can be used in design practice as needed. Finally, a simplified approach for predicting the bending moment versus axial force ( M - N ) interaction curve at the ultimate state is proposed. Highlights: An innovative exposed concrete filled steel tube column base with embedded reinforcing bars is proposed. Eight column base specimens are tested under axial forces and lateral cyclic loading. Failure modes, hysteretic curves, cyclic behavior and strain characteristics are discussed and analyzed. A simplified approach for predicting the M - N interaction curve at the ultimate state is proposed.